2019
DOI: 10.3390/tropicalmed4040127
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Vaccine for Hajj Pilgrims: Compliance, Predictors, and Barriers

Abstract: Background: Major intercontinental outbreaks of invasive meningococcal disease associated with the Hajj occurred in 1987, 2000, and 2001. Mandatory meningococcal vaccination for all pilgrims against serogroups A and C and, subsequently, A, C, W, and Y controlled the epidemics. Overseas pilgrims show excellent adherence to the policy; however, vaccine uptake among domestic pilgrims is suboptimal. This survey aimed to evaluate meningococcal vaccine uptake among Hajj pilgrims and to identify key factors affecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…While pilgrims also receive health promotion messages and information on preventive measures and health services while in KSA, health authorities in the countries of origin are encouraged to provide health education for pilgrims prior to arrival to KSA for Hajj. This is because pre-Hajj health advice is an essential factor contributing to increased compliance with pilgrims’ recommended health measures [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…While pilgrims also receive health promotion messages and information on preventive measures and health services while in KSA, health authorities in the countries of origin are encouraged to provide health education for pilgrims prior to arrival to KSA for Hajj. This is because pre-Hajj health advice is an essential factor contributing to increased compliance with pilgrims’ recommended health measures [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common reasons is a lack of knowledge about vaccines, 114 with some pilgrims being unaware that there is a vaccine available. 115 Equally, availability is an ongoing issue as vaccine shortages are a possibility. 13 Cost is also cited as a reason for not receiving a vaccine, 114 but pilgrims will receive a vaccination if the cost is low or free.…”
Section: The Hajjmentioning
confidence: 99%
“…A follow up study conducted during the 2020 Hajj amidst the COVID-19 pandemic showed no improvement and pilgrims' mean hand hygiene knowledge score remained essentially unchanged (mean score 6.7 (±1.9) vs 6.4 (±1.35) of total 12) [11,13]. Another cross-sectional study conducted in 2017 and 2018 showed that 13.4% of Hajj pilgrims certainly missed meningococcal vaccination and another 4.8% were unsure about their vaccination status, which is a great concern [12].…”
mentioning
confidence: 99%
“…One original study focussed on Hajj pilgrims’ understanding and practice of hand hygiene [ 11 ] and another of meningococcal vaccination [ 12 ]. A cross-sectional study conducted during the 2019 Hajj identified that most pilgrims knew hand hygiene could prevent respiratory and gastrointestinal infections, but many pilgrims did not know about precise hand washing methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation